Robbins and Cotran atlas of pathology - Klatt, Edward C. (Saunders Elsevier, 2010)
An atlas that offers more than 1,500 full-color illustrations which depict the diseases you need to know for pathology courses and USMLE exams. It is suitable for students and professionals alike.